PjBL-MOOCs As Future Models for Vocational High Schools - Mahfudi Sahly Subandi; Syarif Suhartadi; Partono; Andika Bagus Nur Rahma Putra (JPP (Jurnal Pendidikan dan Pembelajaran), 2020)
The purpose of this research is to develop a Project Based Learning model assisted by the Massive Open Online Course. The research design uses Research and Development. The results of the feasibility study of PjBL-MOOCs products include: a) design of 93.75%, b) manuals of 95.13%, c) pictures and charts / charts of manuals of 92.31, d) material of 85%, e ) picture quality in material is 77.1%, f) video is 90.4%, g) test instrument is 90.4%, and h) field trial results is 72%. So that PjBL-MOOCs are feasible to improve student learning outcomes.